Effect of marijuana smoking on lung function change in older ever tobacco smokers. Issue 3 (22nd September 2022) - Barjaktarevic, Igor; Cooper, Christopher B.; Shing, Tracie; Buhr, Russell G.; Hoffman, Eric A.; Woodruff, Prescott G.; Drummond, M. Bradley; Kanner, Richard E.; Han, MeiLan K.; Hansel, Nadia N.; Bowler, Russell P.; Kinney, Gregory L.; et al.
While the impact of marijuana use on symptoms of chronic bronchitis has been widely reported, the association with lung function change over time, especially in those at risk of or with COPD, has been less studied [1–6]. A recent longitudinal analysis of data of the CanCOLD study [2] reported that heavy current or former marijuana smoking defined by ≥20 joint-years (average number of joints smoked per day multiplied by the number of years smoked) was associated with a significantly worse forced expiratory volume in 1 s (FEV1 ) decline over a mean of 5.9 years compared to never smokers of marijuana and tobacco after adjustment for tobacco pack-years [3]. However, questions have been raised concerning the design of this study [4, 5]. To further address whether marijuana smoking impacts lung function change over time in mid-life and older persons, we performed a longitudinal analysis of the trajectory of lung function change in participants with a heavy tobacco smoking history with or without COPD from the Subpopulations and Intermediate Outcome Measures in COPD Study (SPIROMICS). This cohort study of tobacco smokers with COPD failed to demonstrate any clinically significant association of current/former marijuana smoking of any cumulative lifetime amount with a worsening trajectory of FEV1 over an average of approximately 5 years https://bit.ly/3ISoc2c